The same-different task as a tool to study unconscious processing. (February 2021) - Van Opstal, Filip
Abstract : The function of consciousness has often been investigated by looking at the cognitive processes that can (not) be performed without conscious awareness. The most important processes — historically and theoretically — in this context are semantic processing and information integration. Here, I will argue that a subliminal priming version of the same-different task is a perfect tool to investigate these processes because it (i) allows a clear separation between the stimuli that are consciously processed and those that remain unconscious, and (ii) requires the unconsciously presented stimuli to be integrated. An overview of the work that has used the subliminal same-different task to target these processes is presented, and some suggestions for how the task could be used in future work are made. The potential of the subliminal same-different task to elaborate on the cognitive architecture needed to successfully perform a same-different task is also discussed.